Alleviation effect of glycyrrhetinic acid on zearalenone-induced reproductive toxicity in replacement gilts - Che, Li-Tao; El-Sappah, Ahmed H.; Elbaghdady, Heba Allah M.; Ren, Yong-Jun; Wu, Qi-Fan; Zhou, Wan-Hai; Yang, Ya-ru; Guo, Rong-Fu (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated whether glycyrrhetinic acid (GA) can alleviate the reproductive toxicity of Zearalenone (ZEN) in replacement gilts.MethodsEighty Landrace × Yorkshire gilts were randomly assigned to four dietary groups: control (basal diet), ZEN (1 mg/kg), GA (400 mg/kg), and ZEN + GA (1 mg/kg ZEN + 400 mg/kg GA).ResultsThe onset of estrus advanced significantly in all treatment groups, with the GA and ZEN + GA groups showing the most pronounced changes. Puberty onset occurred earlier in the ZEN group and was further advanced by GA supplementation. ZEN exposure impaired uterine and ovarian development, while GA improved organ development and mitigated the abnormalities in the ZEN + GA group. Hormonal analysis revealed that ZEN reduced estradiol (E2) and luteinizing hormone (LH), whereas GA elevated all measured hormones. The ZEN + GA group showed a partial recovery in hormone levels, excluding E2. Histological examination of liver tissue in the ZEN group revealed focal hepatocellular necrosis and lymphocyte infiltration, which GA notably attenuated. ZEN upregulated 3α/3β/17β-hydroxysteroid dehydrogenase (HSD) gene expression in the liver and duodenum, while GA co-administration downregulated most HSD genes except hepatic 3α-HSD.Discussion and conclusionThese findings suggest that GA can alleviate ZEN-induced reproductive toxicity via modulation of endocrine and hepatic metabolic pathways.